2019
DOI: 10.1136/bcr-2018-225685
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing mucoepidermoid carcinoma with eosinophilia of thyroid

Abstract: Sclerosing mucoepidermoid carcinoma of the thyroid was first reported in 1991. This tumour type may develop as associated to Hashimoto thyroiditis. There are two variants of mucoepidermoid carcinoma of thyroid. The conventional and the sclerosing variants. Sclerosing mucoepidermoid carcinoma with eosinophilia of thyroid (SCME) has recently been recognised as a separate disease entity by the WHO. We report a case of SCME in a 62-year-old male patient who presented with a painless anterior neck swelling. Total t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…[8] Other differences include larger epidermoid cell sheets, cystic spaces, and the absence of vascular invasion. [9] Other differential diagnoses of SMECE include primary squamous cell carcinoma of the thyroid, squamous differentiation of other thyroid malignancies like papillary thyroid cancer, medullary thyroid cancer, anaplastic thyroid cancer, nodular sclerosing variety of Hodgkin lymphoma, thyroid malignancies with thymic differentiation, and Langerhans cell histiocytosis. The absence of frequent mitoses, atypia, and presence of sclerosis with eosinophilia differentiate squamous cell thyroid cancer from SMECE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Other differences include larger epidermoid cell sheets, cystic spaces, and the absence of vascular invasion. [9] Other differential diagnoses of SMECE include primary squamous cell carcinoma of the thyroid, squamous differentiation of other thyroid malignancies like papillary thyroid cancer, medullary thyroid cancer, anaplastic thyroid cancer, nodular sclerosing variety of Hodgkin lymphoma, thyroid malignancies with thymic differentiation, and Langerhans cell histiocytosis. The absence of frequent mitoses, atypia, and presence of sclerosis with eosinophilia differentiate squamous cell thyroid cancer from SMECE.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the absence of Reed Sternberg cells and CD15, CD30, and CD 45 positivity in SMECE distinguishes it from the nodular sclerosing variety of Hodgkin's lymphoma, especially in the case of nodal metastasis. [9] SMECE lacks the characteristic nuclear features of the diffuse sclerosing variant of papillary thyroid cancer. Medullary thyroid cancer shows positive staining for calcitonin and the absence of eosinophilia which are absent in SMECE.…”
Section: Discussionmentioning
confidence: 99%
“…Due to abundant sclerosis, FNA findings vary widely and can be deceptively bland 3,4 . Only 11 case reports of SMECE in the literature mention prior FNA and only a subset of those describe the cytomorphology 3‐13 (Table 1). The cellular aggregates seen in smears often have bland cytology including oval nuclei, small nucleoli, occasional grooves, rare nuclear inclusions, and varying amounts of cytoplasm 3,4,6‐10,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE) was first described as a distinct entity from mucoepidermoid carcinoma (MEC) in 1991 by Chan et al 1 Since that description, approximately 56 cases of SMECE have been reported with descriptions of histology 2 . Despite most thyroid nodules having been initially evaluated by fine‐needle aspiration (FNA), there are only 11 cases with descriptions of cytomorphology 3‐13 . No descriptions of SMECE have included concurrent salivary gland neoplasms.…”
Section: Introductionmentioning
confidence: 99%